Comparing between Scopus, Web of Science and Dimensions Indexation: Case of 100 Most Cited Articles on Waqf - Amelia (SMART Insight, 2021)
Islam pays attention to the community’s welfare in a broad sense to be equal to other people, both in the economic, social, political, educational, and other fields. One of the instruments of Islamic teachings regarding this issue is waqf. Waqf is a source of funds that has potential in the economic development of the people. In addition to waqf, there are other sources of social funds such as zakat, infaq, and alms. Even waqf can be used as an endowment for the people that provides benefits for the welfare of society. This study aims to find out the development map and trend of waqf published by well-known journals in Islamic Economics and Finance. The data analyzed were 100 publications indexed in Scopus, Dimensions, and the Web of Science. The data is then processed and analyzed using the VoS viewer application to discover the bibliometric map of waqf’s research development. This study tries to compare between 3 index namely Scopus, Web of Science and Dimensions, whether they provide consistent results or not.